A Model for Developing Teacher Leadership Skills for the University Teachers in Application-Oriented Universities in Taiyuan, Shanxi Province, China - Wang, Senhao; Mhunpiew, Nathara (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
The key to the success of educational reform in universities is the teachers, who are the critical factor in driving school reform, realizing mutual skill enhancement among colleagues, and promoting the growth and success of university students. This study aimed to develop a model to enhance teachers' leadership skills in Application-Oriented Universities in Taiyuan, Shanxi Province, China. The main theories that comprise the conceptual framework of this study are teacher leadership and distributed leadership. This study used a mixed methods research and utilized both qualitative and quantitative research methods. Qualitative data were collected through a systematic literature review and analyzed to integrate the skills needed for teacher leadership and the factors influencing teacher leadership. A questionnaire was developed and distributed to 366 teachers in three Application-Oriented Universities in Taiyuan for quantitative data collection. The findings showed high levels of teacher leadership in the three targeted schools. At the same time, the factors that influence teacher leadership development were found to include collaboration, shared responsibility, empowerment, trust and communication, adaptive and responsive. The survey results also showed that the above five factors positively correlate with improving teachers' leadership skills. Based on these results, experts proposed and validated a model that provides three activities for Application-Oriented University teachers to enhance their teacher leadership skills.